The Use of Directed Reading Thinking Activity (DRTA) to Improve Students Reading Comprehension of the First Grade of Smk Pembangunan Kota Ternate - Mirna Ismail (Jurnal Langua, 2018)
The Purpose of this research is to know the students reading comprehension can be improve by using directed reading thinking activity (DRTA) grade x of SMK Pembangunan Kota ternate .The research of implement classroom action research in two cycles. The subject in this research is the students of grade x of SMK Pembangunan Kota ternate school year 2018-2019 with amount students 20 people. This research is using in one class, each cycle consist of four phase that is: planning, action, observation and reflecting. Based on the result of classroom action research, in Cycle I there are 4 students who have met the KKM while 16 others have not yet reached KKM is due to, pay attention to the student when the teacher’s explanation related implementation learning procedure using Directed Reading Thinking Activity (DRTA) method, activeness each student in identifying text in lucking, students activeness in making question and give the opinions in lucking. As well as the mistake that often student do incomprehension of the text as much 80%. Then in cycle II on the number of students who evaluated the overall reach KKM. This means that increasing students’ comprehension by using Directed Reading Thinking Activity (DRTA) successfully.